Epidemiological trends for functional pancreatic neuroendocrine tumors: A study combining multiple imputation with age adjustment - Luo, Shuaiwu; Wang, Jiakun; Wu, Linquan; Wang, Cong; Yang, Jun; Li, Min; Zhang, Ligan; Ge, Jin; Sun, Chi; Li, Enliang; Lei, Jun; Liao, Yuting; et al. (Frontiers in Endocrinology, 2023)
Purpose: The purpose of this study was to examine trends in the incidence and incidence-based (IB) mortality of functional pancreatic neuroendocrine tumors(F-PNETs), and to identify factors associated with survival times. Methods: Data were obtained from the Surveillance, Epidemiology, and End Results database from 2000 to 2017. Trends in the age-adjusted incidence of F-PNETs and IB mortality were examined using the Joinpoint Regression Program. Statistical analyses were run using chi-square tests, Kaplan–Meier curves, and the Cox proportional hazards model. Multiple imputation was used to deal with missing data. Results: A total of 142 patients with F-PNETs met the study inclusion criteria. It was found that the incidence of F-PNETs decreased over the study period, with an annual percent change (APC) of -2.5% (95% CI [-4.3, -0.5], P<0.05). This decrease was found to be significant for women, and also when limited to cases with distant disease or rare F-PNETs, with APCs of -4.2% (95% CI [-7.4, -0.9], P<0.05), -6.7% (95% CI [-10.4, -2.8], P<0.05), and -9.1% (95% CI [-13.5, -4.4], P<0.05), respectively. The Cox regression analysis revealed that the tumor size, tumor stage, tumor type, and surgical resection were associated with F-PNETs mortality. Conclusions: This was the first population-based epidemiological study of F-PNETs and we found a continual decrease in the incidence of F-PNETs from 2000 to 2017. The prognosis and survival times were closely related to the calendar year at diagnosis, tumor stage, and tumor size.